Local maladaptation due to density-dependent natural selection - Arasimhan, Aaditya N. (IISER Mohali, 2020)
Local maladaptation due to density-dependent natural selection Natural selection usually leads to adaptation, but can also lead to declin- ing population fitness or maladaptation despite evolution at the individual level. In this study, populations subjected to over 250 generations of strong density-dependent natural selection were hypothesised to be locally adapted. I assayed their adult fitness in a common-garden environment to test the local (mal)adaptation hypothesis. Additionally, I performed fitness assays separately in males and females to test whether density-dependent natural selection had any sex specific effects. Males from populations evolving under density-dependent natural selection were maladapted in comparison to their ancestral control populations. In contrast, females showed both local adapta- tion and local maladaptation. Ecological causes for such maladaptation are most likely a combination of poor culture environment, unstable population dynamics and frequency-dependent selection.
Keywords: maladaptation; density-dependent